2020
DOI: 10.3390/microorganisms8081112
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mycobacterial Antibiotic Therapy Induces Remission in Active Paediatric Crohn’s Disease

Abstract: Crohn’s disease is increasing in incidence and prevalence in younger people and is of a particularly aggressive nature. One emerging treatment targets Mycobacterium avium paratuberculosis (MAP), an organism implicated in the causation of Crohn’s disease. This study reviewed a cohort of paediatric patients with active Crohn’s disease treated with Anti-Mycobacterial Antibiotic Therapy (AMAT). Sixteen paediatric patients, the majority of whom had failed conventional immunosuppressive therapy, were treated with AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In most observational studies/case series, the few reported C.difficile infections were mostly in children with recurrent CDI and the rate in children receiving antibiotics did not seem to surpass the incidence reported in IBD populations from current literature [91][92][93]. Only Agrawal et al reported a high percentage of children with CDI, where authors speculate that this is unlikely to be a consequence of antibiotic perturbation of the microbiome since multiple constituents are effective treatments against infection [83]. Turner elaborated on the use of antibiotics in the PRASCO trial (based on non-published data) by explaining that if no response to antibiotics is seen within 3-5 days, the cocktail should be discontinued.…”
Section: Hurdles In the Use Of Antibioticsmentioning
confidence: 98%
See 1 more Smart Citation
“…In most observational studies/case series, the few reported C.difficile infections were mostly in children with recurrent CDI and the rate in children receiving antibiotics did not seem to surpass the incidence reported in IBD populations from current literature [91][92][93]. Only Agrawal et al reported a high percentage of children with CDI, where authors speculate that this is unlikely to be a consequence of antibiotic perturbation of the microbiome since multiple constituents are effective treatments against infection [83]. Turner elaborated on the use of antibiotics in the PRASCO trial (based on non-published data) by explaining that if no response to antibiotics is seen within 3-5 days, the cocktail should be discontinued.…”
Section: Hurdles In the Use Of Antibioticsmentioning
confidence: 98%
“…Remission rate was reached in 21/32 (68%) patients and a significant proportion of the patients achieved normalization of CRP, especially in patients with mild to moderate inflammatory disease involving primarily the terminal ileum and colon [82]. Furthermore, Agrawal and colleagues also showed significant improvement in mucosal healing (SES-CD) in addition to clinical activity indexes in children with moderate to severe CD receiving antimycobacterial antibiotic therapy [83].…”
Section: Use Of Antibiotics In Childrenmentioning
confidence: 99%
“…There is emerging evidence that targeting MAP with antibiotics in Crohn’s disease may be salubrious [ [73] , [74] , [75] ]. Consistent with their in vitro activity, the combination of clarithromycin, rifabutin and clofazimine, has shown efficacy as a primary treatment for Crohn’s disease [ 76 ].…”
Section: Countering Mycobacteria With Bcg And/or Antimicrobial Agentsmentioning
confidence: 99%
“…It is not yet known what initiates the inflammatory processes and the other features of IBD. In one of the IBDs, Crohn's disease, an antibiotic combination targeting Mycobacterium avian subspecies paratuberculosis (MAP) infection has been reported to lead to long-term disease remission [147][148][149][150][151]. Agrawal et al [149] discuss recent promising data and addresses several common objections regarding MAP's role, making a compelling case for the involvement of MAP or similar species.…”
Section: Chronic Inflammatory Disease Featuresmentioning
confidence: 99%